Pemberdayaan masyarakat dalam pengembangan desa wisata Huta Tinggi, kecamatan Pangururan, kabupaten Samosir Sumatera Utara - Zebua, Tri Indriani; Zendrato, Junita Timenikasih; Khairi, Nur Khafiza (Journal of Commerce, Management, and Tourism Studies, 2023)
In order to build the Huta Tinggi Tourism Village, the community is making empowerment efforts. This study intends to identify these efforts as well as supporting and inhibiting elements in the implementation of these empowerment initiatives. This research method uses a qualitative descriptive method. Ways to collect data through observation, documentation, and interviews. The findings show that two types of support were provided for infrastructure development in Jatimulyo Tourism Village: 1) Capital assistance and 2) Infrastructure development assistance, which included beds, speakers, gates, and other items. Relief assistance is arranged by the regional tourism office. 4) Strengthening the management structure, Pokdarwis, and secretariat of the Huta Tinggi Tourism Village 5) Strengthening collaboration between the public, private and non-profit sectors, especially between PLN and PT. Telkom, the Huta Tinggi Village Authority, and the Tourism and Culture Office of Samosir Regency. Supporting elements include itineraries based on local knowledge. While the limiting constraints include insufficient water, lack of tourist attraction, inadequate infrastructure, and low quality and unprofessional human resources.